REQUESTING SPEECH ACT OF UTTERANCES IN OCEAN’S ELEVEN BY STEVEN SODERBERGH: A PRAGMATIC ANALYSIS - Nurul Hasanah; Japen Sarage (Universitas Ahmad Dahlan)
The term sentence and utterance are made different in terms that the former refers to syntactic structure, while the latter points out the actual function of such a structure in real communication. The same things apply to the terms request and requesting. The first term suggests the structural characteristics of sentence asking people to do something while the second term indicates the real sentence causing people to do something. The first deals with formal grammar while the second deals with pragmatics the actual use of language in communication.This article attempts to see requesting in its possible different syntactic forms as parts of speech acts in Ocean’sEleven by Steven Soderbergh. A pragmatic approach is applied since it uses context as a part of linguistic analysis involving the speaker, addressee, time, location, and genre in the conversation. A syntactic form of a sentence only cannot represent the real meaning of intention.The analysis of speech act of the conversation in the film brings us to an understanding that pragmatics encourage us to comprehend different kinds of setting to achieve requesting as a part of language use. Pragmatics as a branch of linguistics reveals mutual understanding between the speaker and the hearer.